2004
DOI: 10.1177/039139880402700808
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Model of Platelet Deposition under Flow Conditions

Abstract: Platelet deposition in resting blood is well researched and understood. However, the influence of hemodynamic parameters such as wall shear rate is less clear. Clinical experience and experiments show an interaction between flow and platelet deposition. But a complete understanding of the flow influence and hence a quantification has not yet been achieved. A well defined experiment of flow dependant platelet depositions is the stagnation point flow. This kind of flow is ubiquitous in the circulatory system, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 7 publications
2
15
0
Order By: Relevance
“…Adhesion of platelets to the vessel wall was assumed to increase the probability of adhesion/activation for other platelets thus imitating the effect of platelet activators release. These models showed good agreement with experimental data [44][45][46] and provided an insight into the role of platelet margination by red blood cells. David et al [44] found that the rate of platelet interaction with the vessel wall should depend on the shear rate.…”
Section: Analysis Of Disease Basissupporting
confidence: 72%
See 4 more Smart Citations
“…Adhesion of platelets to the vessel wall was assumed to increase the probability of adhesion/activation for other platelets thus imitating the effect of platelet activators release. These models showed good agreement with experimental data [44][45][46] and provided an insight into the role of platelet margination by red blood cells. David et al [44] found that the rate of platelet interaction with the vessel wall should depend on the shear rate.…”
Section: Analysis Of Disease Basissupporting
confidence: 72%
“…In particular, a formula was suggested to estimate thrombotic risk by determining the time to vessel occlusion T occlusion : A number of studies used a stagnation point assumption to simulate platelet adhesion both analytically and computationally [44][45][46]. This type of flow is often present in the circulation, in particular, in the recirculation regions.…”
Section: Analysis Of Disease Basismentioning
confidence: 99%
See 3 more Smart Citations